HIDRA: A Distributed Blockchain-Based Architecture for Fog/Edge Computing Environments - Carlos Nunez-Gomez; Blanca Caminero; Carmen Carrion (IEEE Access, 2021)
Nowadays, the fog computing paradigm is being consolidated as a solution for processing the explosion of data generated by lots of common IoT devices connected to the Internet. In contrast to cloud computing, fog computing achieves efficient data processing without incurring large latencies or data transfers to/from the cloud. The distributed nature of fog computing makes the resource orchestration a challenge. Commonly used centralized solutions are of limited utility in this context. Moreover, fog nodes are usually resource constrained, so the implementation of the management modules should be carefully designed in order not to cause excessive overheads. On the other hand, blockchain has proven its utility beyond cryptocurrencies, to support distributed and reliable information storage. When combined with smart contracts it can provide a distributed computer where all the nodes independently and equally contribute to a common global system state, which must be agreed by consensus. This also provides inherent desirable features, such as immutability and transparency. In this work, a novel architecture called HIDRA is presented, aimed at resource orchestration in fog computing environments based on a Ethereum blockchain implementation. A prototype implementation on a testbed composed of single-board computers has been carried out. Results show the low overhead introduced into the system and its ability to perform a coordinated action among fog nodes without the intervention of any central authority.